Pengaruh Pemanfaatan Edmodo Terhadap Hasil Belajar pada Mata Pelajaran Biologi di SMAN 1 Lareh Sago Halaban - Oktomaini, Tila; Supriadi, Supriadi; Zakir, Supratman; Efriyanti, Liza (Indonesian Research Journal on Education, 2023)
This research was motivated by the development of the Covid-19 virus (Corona Virus) or better known as the Corona virus in 2020. Therefore, educators try to use Edmodo as an alternative to the learning media used and to see if the use of Edmodo is working properly, it can be seen from the learning outcomes of students. The useof Edmodo can help students carry out learning well, where the application of Edmodo is easy to use, and helps students understand the teaching materials provided by educators, where the use of Edmodo will be integrated with 21st century abilities (critical thinking skills, creative thinking, communication and collaboration). The type of research used is quantitative with a correlation approach. The population of this study were all students of class X in the science department at SMAN 1 Lareh Sago Halaban. The sample was taken using a 25% proportional stratified random sampling, so the sample in this study was 33 students with the sample selected using the lottery technique, with data collection using a Likert scale questionnaire, for the analysis of thequestionnaire instrument using the Validity and Reliability Test, while the analysis prerequisite test used the normality test. data and linearity test, while for hypothesis testing using simple linear regression analysis test, and Product Moment which requires the hypothesis to be accepted if r count is greater than r table. The results of this study indicate that the results of the calculation of r = 0.865 are in a strong scale. Then the results ofhypothesis testing show that there is an effect of using Edmodo on learning outcomes with a value of r count > r table or r count 0.865 > of 0.344 then H1 is accepted.